High post-season Alnus pollen loads successfully identified as long-range transport of an alpine species. (15th June 2020) - Ghasemifard, Homa; Ghada, Wael; Estrella, Nicole; Lüpke, Marvin; Oteros, Jose; Traidl-Hoffmann, Claudia; Damialis, Athanasios; Buters, Jeroen; Menzel, Annette
Abstract: Alnus pollen is one of the Northern Hemisphere's major aeroallergens. In Central Europe, the genus is represented by three species ( Alnus glutinosa, Alnus incana, and Alnus viridis ). The most common one, A. glutinosa (L.) Gaertn., is widespread in lowland riparian forests, swamps, and forest edges. However, to date is still unknown if all of them - in terms of pollen exposure - are clinically relevant for sensitized individuals. To investigate the associated pollen exposure, particularly also because of long-range transport of airborne pollen, we used backward air mass trajectories and tested this method for the year 2015, based on daily Alnus pollen concentrations at 26 sites in Bavaria, Germany. A. glutinosa 's main pollen season extends from February to March, but a six-day, post-season episode was additionally identified in June. For this episode and all sites, 72-h backward trajectories were calculated at 3-h intervals using high spatial and temporal resolution ERA5 reanalysis data and the HYSPLIT (hybrid single-particle Lagrangian integrated trajectory) model. This backward trajectory method identified air masses from the alpine region in Switzerland and Austria, where relevant areas of A. viridis (Chaix) DC as potential pollen sources exist. These may explain the post-season episode in June, as additionally confirmed by its unique spatial distribution, by a considerably later flowering period, and by repeated long-range transport events as observed in a 23-year pollen time series. Graphical abstract: Image 1 Highlights: Airborne Alnus pollen were recorded at 26 Bavarian sites in 2015. The main alder in Germany, Alnus glutinosa has a pollen season February–March. Recorded pollen at 10 sites in June stemmed from Alnus viridis (green alder). A. viridis originating from the alpine region has later flowering period in June. HYSPLIT trajectory analysis proved the A. viridis long-range transport.